2008
DOI: 10.1111/j.1399-6576.2007.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain and disability 1 year after knee arthroscopic procedures

Abstract: Persistent pain after knee arthroscopy may be a significant health care problem. Age and female gender are independent risk factors for pain and disability 1 year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
0
14
1
2
Order By: Relevance
“…This difference is no longer found at 1 year postoperatively while there is a prevalence of the most important pain in the elderly over 50 years old. In addition, the reduction in quality of life associated with this pain is most important in women at 1 year postoperatively (Rosseland et al, 2008). While the prevalence of pain appears to be greater in women in many areas, pharmacological response (Gear et al, 1999) and non-pharmacological response (Krogstad et al, 1996) to the pain are more important, in particular in the orofacial field.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is no longer found at 1 year postoperatively while there is a prevalence of the most important pain in the elderly over 50 years old. In addition, the reduction in quality of life associated with this pain is most important in women at 1 year postoperatively (Rosseland et al, 2008). While the prevalence of pain appears to be greater in women in many areas, pharmacological response (Gear et al, 1999) and non-pharmacological response (Krogstad et al, 1996) to the pain are more important, in particular in the orofacial field.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of sex and gender differences in pain response after orthopaedic procedures and/or surgery, studies show less conclusive results, somewhat due to lack of standardization in the measurement of pain [14]. However, there is some evidence that women report more pain postoperatively, more intense pain overall, and reduced activities of daily living due to pain compared to men [45,47]. Whether this difference is due to real differences in actual physical response to pain, due to delays in seeking treatment, or due to the influence of social and psychologic factors (ie, men are supposed to tolerate pain better than women) is unknown [25,31,57].…”
Section: Why Are Sex and Gender Important In Research?mentioning
confidence: 97%
“…A survey of studies examining sex differences in post-operative and/or procedural pain (including outpatient surgery [18], knee arthroscopic repair [83, 84], and cholecystectomy [26]) reported either no sex difference or greater sensitivity in females [31]. Rarely is it reported that males display increased sensitivity.…”
Section: Sex Differences In Pain and Morphine Analgesiamentioning
confidence: 99%